Capitalist discourse, technique and populism: a Lacanian approach - Foa Torres, Jorge Gabriel (2013)
This paper seeks to stress some theoretical consequences of the articulation between Lacanian notion of capitalist discourse and Heideggerian technique for analyzing populist issue. The difference between populism and technique resides on the ideological grip involved at each one. On the one hand, if populist´s interpellation addresses to "the people", the technical interpellation addresses to what we can name as the panic mass. On the other hand, the male populism tends to close the symbolic-social field throughout the xenophobic appointing of the distortive element that keeps off the plenitude of the social. On the contrary, the female populism tends to keep on the contingent-unstable nature of hegemonic political articulation.